(untitled) (AYUSHDHARA, 2024)
Anantavata is a Tridosha Pradhana vyadhi afflicting the Manya, Hanu, Shiras, Lalatadi Pradesha characterised by Teevra Ruja, Kampa in the affected parts, Hanu graha, Akshiroga. It can be correlated with trigeminal neuralgia, which is one of the most painful conditions known to the mankind and is most commonly caused due to compression of the root of trigeminal nerve. The pain is so severe that it affects the day-to-day activities of the patients eventually hampering the quality of life. In extreme conditions, it also leads to insomnia, psychological derangements and depression and makes the patient dependent on anti-depressants and analgesics for their lifetime. Hence an intervention, that focuses on the root cause, alleviates the pain, strengthens the affected part and prevents reoccurrence is quintessential. In the view of achieving the same, the following case study was taken up where a female patient aged 57 years, complained of numbness over whole face, shocking sensation over Rt. half of the face, hyperaesthesia and pain in neck radiating to B/L upper limbs since 4 years and was treated with Abhyanga, Parsisheka, Nasya, Shirodhara, Gandusha leading to a significant improvement in the signs and symptoms.